Preparation and characterization of phosphine oxide based polyurethane/silica nanocomposite via non-isocyanate route - KAYAMAN APOHAN, NİLHAN; KARATAŞ, SEVİM (ELSEVIER SCIENCE SA, 2010)
A novel carbonate-modified bis(4-glycidyloxy phenyl) phenyl phosphine oxide (CBGPPO) was synthesized to prepare phosphine oxide based polyurethane/silica nanocomposites. Spherical silica particles were prepared according to Stober method and modified with cyclic carbonate functional silane coupling agent (CPS) to improve the compatibility of silica particles and organic phase. The cyclic carbonate-modified epoxy resins and silica particles were used to prepare hybrid coatings using hexamethylene diamine as a curing agent. The cupping, impact and gloss measurements were performed on aluminum panels, and the tensile test, gel content, thermal and morphological analyses were conducted on the free films. No damage was observed in the impact strength of the coatings. Incorporation of silica and CBGPPO into formulations increased modulus and hardness of the coating making the material more brittle. It was also observed that, the thermal stability of hybrid coatings enhanced with the addition of silica and CBGPPO. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Nanocomposites; Polyurethanes; Structure-property relations; Nanoparticles; FUNCTIONALIZED-SILICA; CHEMICAL FIXATION; EPOXY; POLYMERS; RESINS; NANOPARTICLES; COATINGS; SIZE; CO2